Rumen parameters and intake in goats fed cassava chips and alfalfa - Marques, Raquel; Gonçalves, Heraldo; Meirelles, Paulo Roberto; Brito, Evelyn; Gomes, Helen Fernanda; Oliveira, Giuliana (Revista Ciência Agronômica, 2020)
Pasture-based production systems and alternative foods can be used to reduce goat milk production costs by around 20%.The objective of this study was to examine the effect of substituting the corn and soybean meal of the concentrate with cassava chips and alfalfa, respectively, on the feed intake, fermentation, and rumen degradability parameters of adult, dry, empty, rumen-cannulated Saanen goats reared in a feedlot. The experiment was conducted as a Latin square design in which the following diets were tested: ground corn and soybean meal; cassava chips and soybean meal; ground corn and alfalfa; and cassava chips and alfalfa. The following variables were evaluated: feed intake, rumen parameters, short-chain fatty acid (SCFA) production, and feed degradation kinetics. Inclusion of cassava chips and alfalfa did not influence feed intake or ammonia production. Rumen pH and SCFA production were influenced by the collection times, presenting a high pH (6.29) at the first measurement (07 h 00) and then decreasing, thus influencing SCFA production throughout the day.Acetic acid and total SCFA production were influenced by the diets, with the highest values for the cassava/alfalfa diet (68.03 and 93.64 mM 100 mM-1, respectively) and the lowest values for the corn/soybean diet (55.40 and 76.03 mM 100 mM-1, respectively).Nutrient digestibility was also influenced by diets, with those containing cassava and cassava/alfalfa, providing the greatest effective degradability (57.57 to 0.02 h-1 and 53.49 to 0.05 h-1; 57.25 to 0.02 h-1and 53.26 to 0.05 h-1, respectively). This finding demonstrates that cassava and alfalfa can substitute the corn and soybean meal of concentrates without changing feed intake or the ruminal environment of goats. Rather, this substitution improves acetic acid production and diet digestibility.